Production Of Concrete Pavement Block From Demolished Fired Clay Brick Wastes - Nadzim, Ummi Kalsum Hasanah Mohd (2011)
Construction industry is one of the major industries involved in country‘s development and modernization. Construction and demolition (C&D) wastes constitute a major portion of the total solid wastes production in the world, and most of them are disposed off legally or illegally in any landfills. It is estimated that 13-30% of all solid waste deposited in landfills worldwide comprises C&D waste (Bossink and Brouwers, 1996a). Another problem related to the construction industry is the shortage of natural aggregates and mass generation of fired clay bricks (FCB) from the demolition sites, thus creating environmental problems. Hence, preservation of the environment and conservation of the rapidly diminishing natural resources be the essence of sustainable development.